Rhythms of race : Cuban musicians and the making of Latino New York City and Miami, 1940-1960 - Abreu, Christina D. (Envisioning Cuba., 2015)
"Among the nearly 90,000 Cubans who settled in New York City and Miami in the 1940s and 1950s were numerous musicians and entertainers, black and white, who did more than fill dance halls with the rhythms of the rumba, mambo, and cha cha chá. In her history of music and race in midcentury America, Christina D. Abreu argues that these musicians, through their work in music festivals, nightclubs, social clubs, and television and film productions, played central roles in the development of Cuban, Afro-Cuban, Latino, and Afro-Latino identities and communities. Abreu draws from previously untapped oral histories, cultural materials, and Spanish-language media to uncover the lives and broader social and cultural significance of these vibrant performers"--Provided by publisher.